The SOS and RpoS Regulons Contribute to Bacterial Cell Robustness to Genotoxic Stress by Synergistically Regulating DNA Polymerase Pol II. Issue 3 (1st July 2017) - Dapa, Tanja; Fleurier, Sébastien; Bredeche, Marie-Florence; Matic, Ivan
Abstract: Mitomycin C (MMC) is a genotoxic agent that induces DNA cross-links, DNA alkylation, and the production of reactive oxygen species (ROS). MMC induces the SOS response and RpoS regulons in Escherichia coli . SOS-encoded functions are required for DNA repair, whereas the RpoS regulon is typically induced by metabolic stresses that slow growth. Thus, induction of the RpoS regulon by MMC may be coincidental, because DNA damage slows growth; alternatively, the RpoS regulon may be an adaptive response contributing to cell survival. In this study, we show that the RpoS regulon is primarily induced by MMC-induced ROS production. We also show that RpoS regulon induction is required for the survival of MMC-treated growing cells. The major contributor to RpoS-dependent resistance to MMC treatment is DNA polymerase Pol II, which is encoded by the polB gene belonging to the SOS regulon. The observation that polB gene expression is controlled by the two major stress response regulons that are required to maximize survival and fitness further emphasizes the key role of this DNA polymerase as an important factor in genome stability.